The fundamentals of workplace learning understanding how people learn in working life - Illeris, Knud (Routledge, 2011)
A guide to how people learn in the workplace, and the issues and challenges involved. Examining the fundamental characteristics of workplace learning and unravelling the various influences which affect the success of learners in a work-based environment, it explains how diverse individuals can be encouraged and invited to learn at work.